La sucesión en la empresa familiar industrial: Estudio de casos múltiples. - Mul Encalada, Jennifer; Ojeda López, Ruth Noemi; Jiménez Diez, Olivia (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To analyze the succession process in the industrial family business.MATERIAL AND METHOD: For this qualitative approach, the documentary review, observation techniques, and the multiple case method were used, semi-structured interviews were implemented with the managers of the selected family businesses.RESULTS: They follow the structure of the integrated model for succession in family businesses to explore the cases. In all cases there was an internal succession, an aspect that is given importance is the previous knowledge and the relationships of the successor with clients and suppliers, support is given to professionalization. The most important selection criterion for selecting a successor is experience, the knowledge transferred by the incumbent is important, and work experience.CONCLUSIONS: The lack of succession planning is confirmed and, as on many occasions, this occurs because of the death of the successor. It is recognized that this lack of planning is one of the difficulties faced in the succession process.
Keywords: business; family; succession; planning; family business.